The Position and Legal Authority of Village Regulations within the Hierarchy of National Legislation (Journal of Social And Education Research, 2025)
Village Regulations are legal instruments that play an essential role in the administration of village governance as a manifestation of the principle of village autonomy. However, the position of Village Regulations within the hierarchy of national legislation has been a matter of debate, particularly following the enactment of Law No. 12 of 2011 on the Formation of Laws and Regulations, which does not include Village Regulations in the legal hierarchy. This study aims to analyze the status and legal force of Village Regulations within the national legal system and its implications for village autonomy. The research method employed is normative juridical with statutory and conceptual approaches. The analysis shows that although Village Regulations is not explicitly mentioned in the legislative hierarchy, it retains legal legitimacy under Law No. 6 of 2014 on Villages. Village Regulations has binding legal force within village jurisdictions as long as it does not conflict with higher-level regulations or the public interest. However, the ambiguity of Village Regulations’ position within the legal hierarchy creates potential normative conflicts and legal uncertainty. Therefore, clearer regulations are needed to explicitly define the position of Village Regulations within the national legal system to strengthen the effectiveness of village autonomy.